2000
DOI: 10.1074/jbc.m000967200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of the GAGA Factor Assigns Its Transcriptional Activity to the C-terminal Glutamine-rich Domain

Abstract: GAGA is a nuclear protein encoded by the Trithoraxlike gene in Drosophila that is expressed in at least two isoforms generated by alternative splicing. By means of its specific interaction with DNA, GAGA has been involved in several nuclear transactions including regulation of gene expression. Here we have studied the GAGA 519 isoform as a transcription factor. In vitro, the transactivation domain has been assigned to the 93 Cterminal residues that correspond to a glutamine-rich domain (Q-domain). It presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…It was shown earlier that the C-terminal glutamine-rich domain of GAGA is essential for GAGA-dependent activation both in vitro and in vivo (4). However, the results reported here show that, in addition, the POZ/BTB domain also appeared to have a direct contribution to activation because ⌬POZ GAGA did not efficiently activate the eve promoter.…”
Section: Figcontrasting
confidence: 55%
See 1 more Smart Citation
“…It was shown earlier that the C-terminal glutamine-rich domain of GAGA is essential for GAGA-dependent activation both in vitro and in vivo (4). However, the results reported here show that, in addition, the POZ/BTB domain also appeared to have a direct contribution to activation because ⌬POZ GAGA did not efficiently activate the eve promoter.…”
Section: Figcontrasting
confidence: 55%
“…Many developmentally regulated genes in Drosophila are known to be activated by GAGA (1), and it has been shown that GAGA acts as a transcription activator in vitro or upon transient transfection in cultured S2 cells (2)(3)(4). On the other hand, at the preblastoderm stage, TTK acts as a maternally provided repressor of several pair-rule genes that was proposed to contribute to the establishment of the precise timing of their zygotic expression (5)(6)(7).…”
mentioning
confidence: 99%
“…sistent with the proposal that GAGA factor interactions with GAGAG sites 1 and 2 play an important role in other proteins, including several that have BTB/POZ domains and/or interact with DNA (Espinas et al 2000; Fab-7 boundary activity in early embryos. Unfortunately, in the absence of a sensitized assay system it is not possi- Pointud et al 2001;Pagans et al 2002;Faucheux et al 2003;Mishra et al 2003).…”
Section: R67mentioning
confidence: 95%
“…BACK domains are typically found immediately following the BTB domain in BTB-Kelch proteins but their function is still unclear (Stogios and Privé 2004). Polyglutamine domains are found in several transcriptional regulators including the BTB-zinc finger protein GAGA in which it acts as a transactivation domain (Vaquero et al 2000). It is not yet clear whether EOR-1 functions as a transcriptional repressor and/or activator, as none of its direct targets are known.…”
mentioning
confidence: 99%